The Problem of Spurious Emissions in 5G FR2 Phased Arrays, and a Solution Based on an Upmixer With Embedded LO Leakage Cancellation - Arun Paidimarri; Yujiro Tojo; Caglar Ozdag; Alberto Valdes-Garcia; Bodhisatwa Sadhu (IEEE Open Journal of the Solid-State Circuits Society)
The wireless spectrum is a shared resource. Transmitters are expected to transmit only at their allotted frequency range and not at other frequencies. Transmitters are not perfect, and therefore, there are regulations that limit the transmitted energy outside the intended transmission frequencies. In this article, we provide an overview of the transmit mask requirements for 5G FR2, and the main factors that contribute to unwanted emissions. We then present some key radio architecture and circuit design considerations to help meet these emission requirements. Since the local oscillator (LO) leakage spur is one of the worst offenders, we also introduce an LO cancellation technique in the upmixer. We introduce two actuator circuits to control two independent LO signals at the upmixer output, one resulting from the upconversion from dc to LO, and another resulting from downconversion from 2 LO to LO. These two independent LO outputs then provide 2-D phase and amplitude control and can combine to create an equal and opposite LO signal at the output of the upmixer. The LO cancellation results in better than −57-dBc LO leakage across all candidate frequencies. Finally, we present extensive over-the-air (OTA) measurement validation of the LO suppression across frequencies, signal levels, and 64-element beam steering across a 60 beam steering range.